Cassava leaf disease classification using deep learning and convolutional neural network ensemble - Shahriar, Hasan; Shuvo, Protick Sarker; Fahim, Md. Saidul Haque; Sordar, Md Sobuj; Haque, Md Esadul (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2022.